Optimalisasi Perawatan Sistem Bahan Bakar Guna Menunjang Kinerja Dari Mesin Induk di MV. Thomas Selmer - Figo Pratama; Mustholiq; Utari, Riyadini; Hendro Sulistio; Hermono; Riyadi, Slamet; Setia Budi, Eka; Mafrisal, Mafrisal; Kurniawan, Iwan (Indonesian Journal of Marine Engineering, 2024)
The engine or prime mover on the ship is a device used to move the ship in its operation to carry cargo from one place to another. The fuel system is one of the systems that support the operation of the main engine, therefore it is very important to maintain the quality of the fuel used on board. The purpose of this thesis research is to find out what factors can affect the poor quality of the fuel system, find out what impact is caused by not optimizing the maintenance of the fuel system, and find out how efforts are made to optimize the maintenance of the fuel system to support the performance of the main engine on the MV. Thomas Selmer. The research uses a qualitative descriptive method with fishbone data processing techniques to describe and explain the object under study. Data obtained in this study through observation, and interviews, fishbone diagram is a data processing technique used to improve quality. This diagram shows the relationship between cause and effect of a problem. The results showed that the decline in the quality of HFO on board MV. Thomas Selmer was caused by several things, namely: Not optimal performance of the HFO purifier, Limited fuel oil chemical treatment, and HFO that is not in accordance with ISO 8217 standards. The impact of not optimizing maintenance on the fuel system is a decrease in pump pressure, a lot of sediment in the purifier, an increase in the volume of the sludge tank, and incomplete combustion in the main engine. Carrying out fuel oil analysis and fuel oil treatment procedures in accordance with the manual book and setting point temperatures in accordance with laboratory results are efforts that can be made to maintain fuel quality so that the performance of the main engine becomes optimal.